Proceedings of the 7th International ACM SIGACCESS Conference on Computers and Accessibility 2005
DOI: 10.1145/1090785.1090811
|View full text |Cite
|
Sign up to set email alerts
|

Autism/excel study

Abstract: Five high school students with ASD (autistic spectrum disorder) participating in the Excel/Autism study were able to demonstrate mastery of a set of Excel topics. The Excel curriculum covered approximately the same topics as are covered in the Excel portion of Computer Business Applications, a class for regular education students at Fox Chapel Area High School, a high school in suburban Pittsburgh. The students with ASD were provided with one-on-one tutoring support. Two of the five ASD participants self-initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 5 publications
0
23
0
2
Order By: Relevance
“…Indeed, robots have been shown to be appealing, attracting, and engaging for individuals with ASD. In addition to their mechanical system that is known to attract people with ASD [3,5], they propose simple, repetitive, and predictable behaviors, which can be reassuring for individuals with ASD. SAR focuses on different topics [26]: the design of adapted robots for individuals with ASD, the design of autonomous interaction between the children and the robots, and the evaluations of the therapy proposed for children with ASD.…”
Section: Robots In Asd Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, robots have been shown to be appealing, attracting, and engaging for individuals with ASD. In addition to their mechanical system that is known to attract people with ASD [3,5], they propose simple, repetitive, and predictable behaviors, which can be reassuring for individuals with ASD. SAR focuses on different topics [26]: the design of adapted robots for individuals with ASD, the design of autonomous interaction between the children and the robots, and the evaluations of the therapy proposed for children with ASD.…”
Section: Robots In Asd Therapymentioning
confidence: 99%
“…The ASD literature describes widely the impairments in communication, interaction, emotion recognition, joint attention, and imitation [2]. Children with ASD show a great affinity for robots, computers, and mechanical components [3]. In the field of socially assistive robotics (SAR), robots are used as tools in socialization therapies for children with ASD in order to enhance social engagement, imitation, and joint attention skills [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, robots have been found to be great partners in learning social interaction, and imitation skills [4]. Robots are less complex in their behaviour than human peers offering more predictable and comfortable interaction behaviours [6].Different research areas on robots for therapy for individuals with ASD have been reported in [1]: (1) developing a robot especially designed for individuals suffering of ASD, (2) design of Human-Robot Interaction, and (3) evaluation of the robot in therapies.…”
Section: State Of the Artmentioning
confidence: 99%
“…Individuals with ASD have impaired skills in communication, interaction, emotion recognition, joint attention, and imitation [3]. Many studies showed that children with ASD have a great affinity with robots, computers, and mechanical components [4]. Moreover, in SAR, robots have already been used several times as tools in socialization therapies for children with ASD [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The affinity of children with ASD to mechanical objects is well established [16]. Robots and computers have also been shown to have promise as potential therapeutic and assessment tools, because children with ASD express interest in interacting socially with such machines [15,33,38].…”
Section: Introductionmentioning
confidence: 99%